2022
DOI: 10.1039/d2ra03248a
|View full text |Cite
|
Sign up to set email alerts
|

PdPbAg alloy NPs immobilized on reduced graphene oxide/In2O3 composites as highly active electrocatalysts for direct ethylene glycol fuel cells

Abstract: rGO-modified indium oxide (In2O3) anchored PdPbAg nanoalloy composites (PdPbAg@rGO/In2O3) were prepared by a facile hydrothermal, annealing and reduction method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
1
0
0
Order By: Relevance
“…This phenomenon indicates that they were slightly shifting to a low angle ( Figure 1 B). Results indicated that In 2 O 3 /RGO NCs were further crystallized due to their high peak intensity and sharp peak width, which were matched with earlier studies [ 34 , 35 , 36 ]. The average crystal sizes of pure In 2 O 3 NPs and In 2 O 3 /RGO NCs were 17 nm and 13 nm (estimated by the Debye Scherrer formula), respectively.…”
Section: Resultssupporting
confidence: 90%
“…This phenomenon indicates that they were slightly shifting to a low angle ( Figure 1 B). Results indicated that In 2 O 3 /RGO NCs were further crystallized due to their high peak intensity and sharp peak width, which were matched with earlier studies [ 34 , 35 , 36 ]. The average crystal sizes of pure In 2 O 3 NPs and In 2 O 3 /RGO NCs were 17 nm and 13 nm (estimated by the Debye Scherrer formula), respectively.…”
Section: Resultssupporting
confidence: 90%